2009
DOI: 10.1111/j.1600-0625.2009.00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐killed Propionibacterium acnes is capable of inducing inflammatory responses in skin

Abstract: The etiology of acne is a complex process, and acne is one of the most common skin disorders affecting millions of people. The pathogenesis of acne is closely associated with the bacterium, Propionibacterium acnes which was previously known as Corynebacterium parvum. Both viable and non-viable P. acnes ⁄ C. parvum have been shown to induce an immunostimulatory effect in vivo, suggesting that even dead bacteria continue to activate an inflammatory response. Acne treatments with lasers or devices, induce a bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 34 publications
3
23
0
1
Order By: Relevance
“…A large, randomized controlled trial comparing five antimicrobial regimens noted that clinical efficacy of oral antibiotics was less in those with resistant strains, suggesting that antibiotics may work through a direct antimicrobial as well as anti‐inflammatory effect. This is a concept that the majority of experimental studies have supported, although not all 152–155 . Similar bacterial resistance has been seen in other studies as well, 156,157 and in vitro experiments have shown that resistance may be due to the formation of biofilms 158 .…”
Section: Infectionsupporting
confidence: 66%
“…A large, randomized controlled trial comparing five antimicrobial regimens noted that clinical efficacy of oral antibiotics was less in those with resistant strains, suggesting that antibiotics may work through a direct antimicrobial as well as anti‐inflammatory effect. This is a concept that the majority of experimental studies have supported, although not all 152–155 . Similar bacterial resistance has been seen in other studies as well, 156,157 and in vitro experiments have shown that resistance may be due to the formation of biofilms 158 .…”
Section: Infectionsupporting
confidence: 66%
“…The pathogenetic role of IL-8 has been postulated, at least in part, in neutrophil-related skin diseases such as psoriasis [49,50], palmoplantar pustulosis [50] and acne [48,51,52]. Propionibacterium acnes is feasible for inducing IL-8 production in various cell types including NHEKs [52,53].…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 99%
“…Throughout the activation of TLRs, PARs and antimicrobial peptides, P. acnes upregulates the secretion of different proinflammatory cytokines (IL‐1α, IL‐1β, IL‐6, IL‐8, IL‐12, TNF‐α or granulocyte macrophage colony stimulating factor) by human keratinocytes, sebocytes or macrophages and strongly activates the inflammasome of human peripheral neutrophils …”
Section: P Acnes and Inflammationmentioning
confidence: 99%